The Relationship between Environmental Sanitation and the Incidence of Dengue Hemorrhagic Fever (DHF) in Indonesia - Yulianti; Hidayani, Wuri Ratna (Journal of Public Health Sciences, 2022)
Dengue Hemorrhagic Fever (DHF) was a disease caused by dengue virus belonging to the Arthropod-Borne Virus, which were transmitted through the bite of misquitoes of the genus Aedes, especially Aedes aegypti. The Indonesian Ministry of Health noted that the number of dengue cases in Indonesia from 2018 to 2019 increased significantly. The number of dengue cases as of January 2018 was 6,800 cases with a death toll of 43 people. In early January 2019, there were 13,683 cases with 132 deaths. Cumulatively as of June 21. 2020 there were 68,753 cases. The emergence of dengue disease were related to environmental conditions and community behavior. Research purposes known a relationship between environmental sanitation and the incidence of dengue hemorrhagic fever (DHF) in Indonesia. Reseacrch methodology was a secondary research with a literature review design by doing a search on Google Scholar through the stages of research according to the eligibility criteria. Research result obtained 7 journal that discuss environmental sanitation related to the incidence of dengue hemorrhagic fever (DHF). Of the 7 journals that discuss water reservoirs (TPA) there were 3 journals, 2 journals for garbage disposal, and 4 journals for 3M plus action. The results showed that there were a relationship between when the variable and the occurrence of dengue hemorrhagic fever (DHF). There were a relationship beteween environmental sanitation (water storage, garbage disposal, and 3M Plus measures) with the incidence of dengue hemorrhagic fever (DHF).